Prescription Drug Misuse in “Clubbers” and Disco Goers in Ibiza - di Giannantonio, Massimo; Negri, Attilio; Schiavone, Stefania; Vannini, Chiara; Pettorruso, Mauro; De-Giorgio, Fabio; Verrastro, Valeria; Trabace, Luigia; Corbo, Mariangela; Gottardo, Rossella; Camuto, Cristian; Mazzarino, Monica; et al. (Frontiers in Psychiatry, 2020)
Background: Prescription drug misuse and its related risks are considered a worldwide public health issue. Current trends show that the extent of such phenomenon may not be limited to subjects with psychiatric disorders, as it also spreads to dance party and nightclub attendees, who often consume prescription drugs in combination with alcohol and psychoactive substances. This study aims to report the sociodemographic data and the psychiatric and clinical features of a sample of clubbers reporting prescription drugs use. Methods: Patients admitted to the psychiatry ward of the Can Misses Hospital in Ibiza were recruited for the study during a span of four consecutive years (2015–2018). The inclusion criteria were age 18–75 years old and the intake of psychoactive substances or more than five alcohol units during the previous 24 h. Substance use habits, psychopathological features, and use of unprescribed pharmaceuticals were investigated. Urine samples were collected and analyzed using gas chromatography/mass spectrometry. Results: A total of 110 subjects with psychoactive substance intoxication were recruited for the study. Among these, 37 (40%) disclosed the use of prescription drugs without medical supervision. The most common compounds were benzodiazepines (66%), antiepileptic drugs (8%), antidepressants (6%), opioids (6%), antipsychotics (6%), stimulants (6%), and non-steroidal anti-inflammatory drugs (NSAIDs, 2%). Prescription drug misuse was negatively associated with the use of psychodysleptics (two-tailed Fisher's exact test p = 0.018, ρ = −0.262). Conclusions: The use of prescription drugs is also common among clubbers, usually characterized by low propensity to be prescribed benzodiazepines, antipsychotics, or antidepressants. Prescription drugs may be an alternative to classic and novel psychoactive compounds or may be used to tamper and self-medicate the effects determined by the use of substances. Party goers should be adequately informed about possible risks of co-intake of psychoactive substances and prescription drugs to prevent serious medical and psychiatric consequences.